Vascular Complications following Isolated Limb Perfusion for Local Recurrence of Extremity Melanoma: A Case Report and Literature Review. (29th June 2011) - Trezzi, M.; Parolari, A.; Loardi, C.; Alamanni, F.
Abstract : Introduction . To evaluate the role of hyperthermic isolated limb perfusion (HILP) in arterial thrombosis following melanoma-soft tissue sarcoma chemotherapy. Report . Here is presented one case of iliac-common femoral artery subacute thrombosis and a review of the appropriate literature performed using a MEDLINE search. Acute/subacute arterial occlusion is one of the most feared vascular complications of HILP, located nearly always in the external iliac-femoral artery axis, being those vessels cannulated for perfusion. Conclusions . The small number of reported cases indicates either the rarity of this complication or unawareness of its existence. The true incidence of this complication is probably underreported.